Penerapan Pola Hidup Sehat Melalui Kebersihan Lingkungan Sekolah dalam Membentuk Karakter Siswa di SDN Kejapanan III Gempol Pasuruan - Febriyani, Lailatul Fariha; El-Yunusi, Muhammad Yusron Maulana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by the fact that a healthy lifestyle through a clean school environment will shape the character of students at SDN Kejapanan III Gempol Pasuruan. The aim of this research is to determine the character of students that will be formed in implementing a healthy lifestyle through a clean school environment. The method used in this study is qualitative. The research instruments used are observations and speeches in maintaining or actively carrying out environmental cleanliness such as benefits and consequences in the implementation of a healthy lifestyle through school cleanliness. The sample used in this study is all students at SDN Kejapanan III Gempol Pasuruan. The data produced was analyzed in a qualitative descriptive manner. The result of this study is that the application of a healthy lifestyle through the cleanliness of the school environment can shape the character of students, namely discipline, responsibility, caring for the surrounding environment and forming a spirit of loving a healthy and clean environment in the school environment. By maintaining the cleanliness of the school environment, students will be comfortable in learning at school. The formation of disciplined student character through a healthy lifestyle through school cleanliness is to make students concerned and sensitive if the school environment is felt dirty so that they are moved to clean the surrounding environment